DIFUSI INOVASI DALAM TRANSFORMASI PENDIDIKAN TEKNOLOGI DAN KEJURUAN: TANTANGAN DAN IMPLEMENTASI DI SMK - Naufal Naufal; Hasan Maksum; Doni Novaliendry (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
The transformation of Technical and Vocational Education and Training (TVET) in Vocational High Schools (Sekolah Menengah Kejuruan/SMK) has become a strategic agenda in responding to changing workforce competency demands driven by digitalization, automation, and industrial dynamics. However, various vocational education innovations formulated through national policies are not always optimally implemented at the school level. This study aims to analyze the transformation of SMKs from a diffusion of innovations perspective by examining the types of innovations that have emerged, patterns of adoption within educational institutions, and factors influencing the success and constraints of their implementation. The study employs a qualitative approach through a targeted literature review and policy document analysis, which are thematically synthesized to identify general trends and dynamics in the adoption of vocational education innovations. The findings indicate that SMK transformation occurs in the form of innovation packages encompassing the strengthening of link and match, the implementation of teaching factory models, industry-based project learning, competency certification, and the digitalization of learning. Innovation adoption tends to be partial and gradual due to differences in human resource readiness, infrastructure availability, the quality of industry partnerships, and change management at the school level. Innovations are adopted more rapidly when their benefits are directly perceived, aligned with the practical culture of SMKs, trialable on a limited scale, and easily observable in their outcomes. This study concludes that accelerating TVET transformation in SMKs requires diffusion strategies oriented toward strengthening teacher capacity, systematic change management, and the development of sustainable school–industry networks. ABSTRAKTransformasi Pendidikan Teknologi dan Kejuruan (PTK) pada Sekolah Menengah Kejuruan (SMK) menjadi agenda strategis dalam merespons perubahan kebutuhan kompetensi dunia kerja yang dipicu oleh digitalisasi, otomasi, dan dinamika industri. Namun, berbagai inovasi pendidikan vokasi yang dirancang melalui kebijakan nasional tidak selalu terimplementasi secara optimal di tingkat sekolah. Penelitian ini bertujuan menganalisis transformasi SMK melalui perspektif difusi inovasi dengan menelaah bentuk inovasi yang berkembang, pola adopsi di satuan pendidikan, serta faktor-faktor yang memengaruhi keberhasilan dan hambatan implementasinya. Penelitian menggunakan pendekatan kualitatif melalui kajian literatur terarah dan analisis dokumen kebijakan, yang disintesis secara tematik untuk mengidentifikasi kecenderungan umum dan dinamika adopsi inovasi pendidikan vokasi. Hasil kajian menunjukkan bahwa transformasi SMK berlangsung dalam bentuk paket inovasi yang mencakup penguatan link and match, penerapan teaching factory, pembelajaran berbasis proyek industri, sertifikasi kompetensi, serta digitalisasi pembelajaran. Pola adopsi inovasi cenderung bersifat parsial dan bertahap akibat perbedaan kesiapan sumber daya manusia, ketersediaan infrastruktur, kualitas kemitraan industri, serta tata kelola perubahan di tingkat sekolah. Inovasi lebih cepat diadopsi ketika manfaatnya dirasakan secara langsung, selaras dengan kultur praktik SMK, dapat diuji coba dalam skala terbatas, dan hasilnya mudah diamati. Penelitian ini menyimpulkan bahwa percepatan transformasi PTK di SMK memerlukan strategi difusi inovasi yang berorientasi pada penguatan kapasitas pendidik, pengelolaan perubahan yang sistematis, serta pengembangan jejaring sekolah–industri yang berkelanjutan.